Peningkatan Sikap Ilmiah Siswa melalui Guided Inquiry Berbantuan Media Papan Putar pada Tema Pahlawanku Kelas IV - Safa Anindiya Pratista Putri Candra Dewi; Fina Fakhriyah; Imaniar Purbasari (Journal Prakarsa Paedagogia, 2019)
This research aims to describe how many the increase scientific attitudes of students and teacher skills through guided inquiry assistance by circle board properties on pahlawanku theme in fourth grade of SD 1 Margorejo. Scientific attitudes are student attitudes that appear through scientific activities in learning. Guided inquiry is model of learning that involves students actively in learning process through research activities and inquiry systematically to answer a problem. Action hypotheses in this research are the application of guided inquiry learning models assistance by circle board properties can increase scientific attitude of students on pahlawanku theme in fourth grade of SD 1 Margorejo. This classroom action research conducted in fourth grade class of SD 1 Margorejo with 20 students as subject. Available two cycles in this research, each cycle consist of four stages, they are planning, implementation, observation, and reflection. The dependent variable is scientific attitudes, meanwhile the independent variables are guided inquiry learning models and circle board properties. Aggregation data technique that used is interview, observation, test, and documentation. The analyses data in this research is quantitative and qualitative analyses data. The result of this research shows that there is increase of student scientific attitudes measured by three aspects of learning. Scientific attitudes in cycle I on knowledge aspect is65%, attitude aspects is 2,81, and skill aspects is 2,96. The cycle II increased to knowledge aspect is 85%, attitude aspects is 3,33, and skill aspects is 3,38. It proves that student scientific attitudes can increased through guided inquiry assistance by circle board properties on pahlawanku theme fourth grade of SD 1 Margorejo. Based on the result of this classroom action research that have done in fourth grade of SD 1 Margorejo, the research concludes that student scientific attitudes can increase through guided inquiry assistance by circle board properties on pahlawanku theme fourth grade of SD 1 Margorejo. Therefore, the researcher gives suggestions are on applying guided inquiry learning models assistance by circle board properties, teacher must be more competent and innovative in improving student participations